Peronism in power: the first and failed experience of government in Formosa, 1973 - Servetto, Alicia (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2002)
This article aims at analyzing the particular case of the province of Formosa, the first province to be intervened six months after the installation of the new constitutional government and one month after the inauguration of President Perón. Antenor Gauna and Ausberto Ortíz was the governmental formula that led Peronism to victory with 70.2% of the votes, in the second round. It was the first Peronist government in Formosa to conquer power after its provincialization in June 1955. A young, frontier and peripheral province, it was characterized by its discontinuous political experiences and its short history of participation and institutional representation. Its marginality in the economic and social map of Argentina was also reflected in the political literature of the seventies: none of the classic texts mentioned the problems of Formosa and, even less, referred to the internal process that ended with the federal intervention. Indeed, in the particular case of the province of Formosa, it is possible to observe different lines of conflict which, although in some aspects, are reduced to the intra-Peronist conflict, the internal dispute for power was also articulated with the mobilization of other social actors that had become the main mobilizing force in the province, such as the Unión de Ligas Campesinas de Formosa (ULICAF).